Brand Management in Medical Schemes: Outsourcing and Website Dynamics - Willie, Michael Mncedisi (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
Outsourcing has become a widely adopted strategy to enhance operational efficiency in the rapidly changing medical schemes sector. However, it also poses challenges in maintaining brand identity and differentiating between medical schemes and third-party administrators. This study examines the impact of outsourcing on brand extension and website development within medical schemes, utilizing a mixed-method research approach that includes a comprehensive literature review and detailed case study analyses. It explores the distribution of administration fees, identifying distinct patterns and potential anomalies in fee rates across various operational models. Additionally, the research investigates complaints about medical scheme websites, emphasizing the crucial role of accurate and reliable online resources in ensuring member satisfaction. Complaints about these websites predominantly concern failures to update content and discrepancies in network information, each accounting for 28% of the issues reported. Other concerns include transparency, accuracy of information, claims disputes, and unmet coverage expectations, underscoring the need for significant improvements in website management to build trust and enhance the member experience. The analysis also highlights that schemes managing operations internally incur higher administration expenses than those outsourcing these functions. The study recommends that medical schemes focus on clearly distinguishing themselves from third-party administrators in branding and communication by developing distinct brand identities that reflect their unique value propositions and services. There is a critical need to improve the functionality and transparency of scheme websites to enhance member engagement and satisfaction, especially for schemes with their unique sites. This study provides a comprehensive overview of the importance of brand identity and customer service in shaping the healthcare experience for members of medical schemes, offering practical recommendations for industry stakeholders and policymakers.